Geosocial Media as a Proxy for Security: A Review - Zhigang Han; Songnian Li; Caihui Cui; Daojun Han; Hongquan Song (IEEE Access, 2019)
Security issues such as natural disasters and terrorist attacks have attracted increasing global concern and attention. How to effectively detect security events has become worrisome to countries worldwide. Advances in mobile Internet technology have led to hundreds of millions of users using social media daily to post microblogs, text messages and multimedia information, generating enormous amounts of social media data that reflect people's social behaviors. Studies have proven that the timely intelligence can be extracted from these data. In particular, geosocial media when combined with location information can be used as a proxy for security event detection and security situational awareness. This paper provides a synopsis of the geosocial media data and the related processing/analysis methods used for detecting security events, and summarizes the general framework of security-related analyses based on geosocial media. Four major categories of analysis methods and application cases, including natural language processing, social network analysis, location inference and geospatial analysis, and image or video understanding, are discussed in detail. The paper concludes with possible future directions and areas of research that could be addressed and investigated. We hope to provide a clarion call to the scientists, practitioners, and other stakeholders to enhance the capabilities and accuracy of security events detection and security situational awareness and assessment using geosocial media.